Reg-II Is an Exocrine Pancreas Injury-Response Product That Is Up-Regulated by Keratin Absence or Mutation - Zhong, Bihui (The American Society for Cell Biology, 2007)
The major keratins in the pancreas and liver are keratins 8 and 18 (K8/K18), but their function seemingly differs in that liver K8/K18 are essential cytoprotective proteins, whereas pancreatic K8/K18 are dispensable. This functional dichotomy raises the hypothesis that K8-null pancreata may undergo compensatory cytoprotective gene expression. We tested this hypothesis by comparing the gene expression profile in pancreata of wild-type and K8-null mice. Most prominent among the up-regulated genes in K8-null pancreas was mRNA for regenerating islet-derived (Reg)-II, which was confirmed by quantitative reverse transcription-polymerase chain reaction and by an anti-Reg-II peptide antibody we generated. Both K8-null and wild-type mice express Reg-II predominantly in acinar cells as determined by in situ hybridization and immunostaining. Analysis of Reg-II expression in various keratin-related transgenic mouse models showed that its induction also occurs in response to keratin cytoplasmic filament collapse, absence, or ablation of K18 Ser52 but not Ser33 phosphorylation via Ser-to-Ala mutation, which represent situations associated with predisposition to liver but not pancreatic injury. In wild-type mice, Reg-II is markedly up-regulated in two established pancreatitis models in response to injury and during the recovery phase. Thus, Reg-II is a likely mouse exocrine pancreas cytoprotective candidate protein whose expression is regulated by keratin filament organization and phosphorylation.